Proceedings 16th International Parallel and Distributed Processing Symposium 2002
DOI: 10.1109/ipdps.2002.1016665
|View full text |Cite
|
Sign up to set email alerts
|

Modular interconnection system for optical PCB and backplane communication

Abstract: This paper presents a way of building modular systems with a powerful optical interconnection network. Each module, placed on a Printed Circuit Board (PCB), has a generic optical communication interface with a simple electronic router. Together with optical switching using micro-electromechanical system (MEMS) technology, packet switching over reconfigurable topologies is possible. The interconnection system gives the possibility to integrate electronics with optics without changing existing PCB technology. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This makes the use of MOEMS components very appealing, since they can provide robustness and compact solutions to a low cost and adds support for the varying asymmetric traffic patterns that can emerge in the application. In our previous work [8,9] we have investigated how optical network architectures can be incorporated into parallel computing and communication systems. We have showed that the power of reconfigurability in communication equipment is best applied in the backplane where the highest gain is achieved to the lowest cost [9].…”
Section: Introductionmentioning
confidence: 99%
“…This makes the use of MOEMS components very appealing, since they can provide robustness and compact solutions to a low cost and adds support for the varying asymmetric traffic patterns that can emerge in the application. In our previous work [8,9] we have investigated how optical network architectures can be incorporated into parallel computing and communication systems. We have showed that the power of reconfigurability in communication equipment is best applied in the backplane where the highest gain is achieved to the lowest cost [9].…”
Section: Introductionmentioning
confidence: 99%